1986
DOI: 10.1111/j.1440-1681.1986.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Purine‐related Compounds on Pancreatic Exocrine Secretion in the Dog

Abstract: The effects of adenosine, adenosine 5'-triphosphate (ATP) and inosine on pancreatic exocrine secretion were investigated in the vascularly isolated and self-haemoperfused dog pancreas. Drugs were injected close-arterially (i.a.) in a single bolus. These three purine-related compounds per se did not affect resting rate of pancreatic secretion and the concentrations of protein and bicarbonate in the resting juice. Graded doses of adenosine (0.1-1.0 mg, i.a.) and ATP (0.1-1.0 mg i.a.) administered 1 min prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Figure 3 shows that ionomycin (0.5 (17). We therefore tested the effects of ATP, ADP, and AMP on 1251 efflux from BxPC-3 cells.…”
Section: Effect Of Ionomycin On 12'1 Effluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows that ionomycin (0.5 (17). We therefore tested the effects of ATP, ADP, and AMP on 1251 efflux from BxPC-3 cells.…”
Section: Effect Of Ionomycin On 12'1 Effluxmentioning
confidence: 99%
“…We used an 1251 efflux assay to monitor the anion permeability of BxPC-3 cells. For the efflux experiments, BxPC-3 cells (passages [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were seeded at a density of lo6 celldm1 onto 52-mm plastic culture dishes and grown for a period of 8 days, by which time they had reached confluency.…”
Section: 5~ Efflux Experimentsmentioning
confidence: 99%
“…This finding supports nicely earlier studies performed on dog whole pancreas. Although adenosine decreased blood flow, it enhanced secretinstimulated HCO K 3 and fluid secretion (Yamagishi et al 1985(Yamagishi et al , 1986. A pharmacological study indicated that it was the A 2A adenosine receptor that was involved in this secretory response in dog pancreas (Iwatsuki 2000).…”
Section: Pancreatic Ductsmentioning
confidence: 99%
“…Indeed, adenosine response was not found on isolated rat acini. In intact dog pancreas, adenosine modulated secretion evoked by secretin [39,40]. Using agonists and antagonists for adenosine receptors, it was implicated that A 2A receptors were involved in HCO À 3 secretory response [16].…”
Section: Introductionmentioning
confidence: 99%